Minat Mahasiswa terhadap Bahasa Arab: Studi pada Program Pendidikan Ulama Tarjih FakultasAgama Islam Universitas Muhammadiyah Malang - Fathor Rahim (Universitas Muhammadiyah Malang, 2019)
This article explains about the interest of students Program Pendidikan Ulama Tarjih University of Muhammadiyah Malang (PPUT UMM) towards Arabic language education program. The study of the interests of prospective ulama students in Muhammadiyah is important, because: First, it has never been done, especially relating specifically to improving the ability of Arabic as a